Preskrba s tkivi na Očesni kliniki v Ljubljani - Schollmayer, Petra (Zdravniški vestnik, 2012)
Aim: To present the eye banking at the Eye Hospital Ljubljana. Methods: Reviewof the documentation of the Eye Bank at the Eye Hospital, University Medical Centre Ljubljana in the period from 1 July 2009 to 31 December 2011. Results: The Eye Bank activities at the Eye Hospital Ljubljana include retrieval, evaluation, storage and transplantation of corneal and scleral tissue, as well as of amniotic membrane. In the observed 30 months after the accreditation process, 135 retrievals were performed all over the country, harvesting 262 corneas. Mean donor age was 53.4 years, mean recipient age was 58 years. The death-to-preservation time (DPT) in postmortem donors was 8.3 hours on average, while the storage time was 2.8 days on average. Of the harvested corneas, 148 (56.5 %) were transplanted. The tissue was not selectedfor transplantation because of poor endothelium (19.5 % of all harvested corneas), positive serology (9.5 %), stromal opacities (7.2 %), extensive epithelial defect with stromal edema (4.2 %), significant arcus senilis (3 %) or other reasons (0.8 %). Indications for transplantation included: keratoconus (26.3 %), postoperative bullous keratopathy (24.3 %), post-infectious scar (12.2 %), post-traumatic scar (9.5 %), late graft failure(9.5 %), Fuchs' endothelial dystrophy (4.7 %), perforated corneal ulcer(4.7 %), chemical corneal injury (2 %) and corneal dystrophies other thanFuchs (4 %). Conclusions: The Eye Hospital of Ljubljana has accredited eyebanking activity with controlled and well-documented procedures, and an increasing number of retrievals and transplantations.
Keywords: amnijska membrana; očesna banka; presaditev; roženica; sklera